Bioactive pentacyclic triterpenes from the root extract of Ampelopsis japonica (Thunb.) Makino. (October 2021) - Niu, Chao; Wang, Hui; Zhang, Zhen-Zhen; Yang, Lan-Ping; Zhai, Yang-Yang; Liu, Zhi-Qiang; Liu, Zhen-Zhen; Zhang, Bao-Bao; Zhou, Jing-Chun; Wang, Zhen-Hui
Graphical abstract: Ampelopsis japonica (Thunb.) Makino. Highlights: Two new pentacyclic triterpenes were isolated from Ampelopsis japonica (Thunb.) Makino. Inhibitory activity were evaluated for the isolated pentacyclic triterpenes. Compounds 2, 4 –7 showed potent inhibitory activity on NO production. Abstract: Two new Δ 12 ursene-type pentacyclic triterpenes containing the trans -feruloyl moiety (1, 2 ), together with five known pentacyclic triterpenes (4, 5, 6, 7 ), were isolated from a Ampelopsis japonica (Thunb.) Makino root ethanol extract. Their structures were elucidated by spectroscopic techniques (IR, UV, MS, 1D, 2D NMR). The isolated compounds 2, 4–7 exhibited potent inhibitory activity on NO production in LPS-activated RAW 264.7 macrophage cells by using MTT assays, with inhibition rates of 33.53–56.37 %.